Recursos minerales marinos en las rías gallegas y en la plataforma continental adyacente. - Rey, D.; Vilas, Federico; Bernabéu, A.M.; Manso, F.; Méndez, G. (Journal of Iberian Geology, 2000)
The natural wealth of the Galician rias and adjoining platform is not constrained to their well know fisheries. Their marine mineral resources, such as aggregates, placers, marine salt, phosphorites, hydrocarbons and gas hydrates, also have very significant intrinsic economic value. Despite a number of marine salt exploitations of historical relevance, the economic importance of marine mineral mining in Galicia, at present day, is limited to aggregates for beach renourishment. A complex interaction of legal, technological and economical factors has inhibited the development of other resources. However, the new international political and economical order has provided a very different scenario that favours their exploitation. Sensitive to this change, the relevant institutions have put in place evaluation programs for some of these resources, whose results will be shown here. This is the case of hydrocarbons, of strategic energy interest, or placers a source of metals and rare-earth elements for the new materials industry. In this sense it is desirable that alternative energy resources like gas hydrates, or strategically interesting resources for agriculture like phosphorites will be adequately evaluated in the next few years. Only a complete evaluation of the true economical importance of all the marine mineral resources in Galicia will allow adequate long-term planning of successful sustained development policies.